Aqueous microwave-assisted one-pot synthesis of N-substituted rhodanines - Nitsche, Christoph; Klein, Christian D. (Tetrahedron letters, 2012)
Two aqueous, one-pot, microwave-assisted methods for the rapid synthesis of N-substituted rhodanines from amine substrates are described. Alkyl- and benzylamines could be converted into the corresponding rhodanines with an atom-efficient one-pot, three-step protocol based on carbon disulfide and chloroacetic acid in short reaction times and good to excellent yields. An alternative, microwave-assisted one-pot, one-step protocol using bis(carboxymethyl)trithiocarbonate in water was developed for the synthesis of N-arylrhodanines from anilines.
Gesehen am 29.05.2018